Estudo molecular e biológico de um isolado viral de Physalis peruviana proveniente do Estado de Santa Catarina - Fernandes, Sérgio Bruno (2018)
Physalis (Physalis peruviana L.) has been considered a good alternative for small farmers in the Southern region of Brazil, which presents favorable climatic conditions. Besides that, this plant produces fruit with high market value, with nutraceutical qualities and low production cost, allowing growers to reach several market niches. However, the physalis faces great challenges due to its recent introduction in Brazil, since there is little information on the control of phytopathogens that could jeopardize the crop yield, such as viral diseases. Recently, a viral isolate called BRSC2017 was detected in P. peruviana plants, grown in the Santa Catarina State, Brazil, presenting mosaic, foliar deformation and stunting. These symptoms suggested the presence of Potato virus Y (PVY), which is common in solanaceous plants. However, samples sent to the Laboratory of Molecular Virology, for virus diagnosis, were DAS-ELISA and RT-PCR negative, when tested with antisera and primers specific for PVY. Inoculation in diagnostic species also induced symptoms different from those caused by PVY, and the virus was not transmitted by Myzus persicae Sulz. Later observation under the electron microscope showed isometric particles, with about 30nm in diameter, confirming these results. Using random primers, a fragment containing 673bp was amplified by RT-PCR, sequenced and analyzed. When the nucleotides of BRSC2017 were compared with genomes of the viral isolates available in GenBank, the greatest nucleotide identity (69%) occurred with ORF 2B, which encodes the RNA-dependent RNA polymerase (RdRp) of Velvet tobacco mottle virus (VTMoV), a Sobemovirus species. The VTMoV is present in Australia but has not yet been described in Brazil. However, based on the taxonomic criteria for species demarcation in the genus Sobemovirus, the lower identity needed to be considered the same species must be 75%. The complete sequencing of the BRSC2017 genome will allow a definitive identification of this viral isolate.